Peranan Alumni Perguruan Tinggi Kagamaan Islam di Tengah-Tengah Masyarakat - Suhardin, Suhardin (AL-WIJDÃN Journal of Islamic Education Studies, 2018)
The focus of this research is how the role of alumni of Islamic State Islamic College; the first sub-focus, how acceptibilty PTKI UIN Suska Riau, especially alumni of Islamic Religious Education (PAI) Faculty of Eductional and Teacher Training (FTK) in the community; Second, how to coaching the guidance of UIN Suska Riau Student coaching, especially alumni of Islamic Education (PAI) Faculty of Educational and Teacher Training (FTK); Third, how the development of curriculum of PTKI UIN Suska Riau, especially alumni of Islamic Religious Education (PAI) Faculty of Educational and Teacher Training (FTK); Fourth, how the structure of PTKI UIN Suska Riau program, especially alumni of Islamic Religious Education (PAI) Faculty of Educational and Teacher Training (FTK); Fifth, how the distribution of alumni of PTKI UIN Suska Riau, especially alumni of Islamic Religious Education (PAI) Faculty of Educational and Teacher Training (FTK) in the community; The method used in this research is qualitative research, the researcher collects the information, documentation and data to the authorized party, with procedural choaching, legality, confirmation to the data source. The findings presented in this study. The first PAI of 165 has given a graduation of 5,775 (five thousand seven hundred seventy-five), the alumni have been traced with a study tracer with excellent grades of 79.5 both 18.28 and enough 2.19 of the integrity component, professionalism, tahfidz, ICT empowerment, communication, cooperation, and self-development Second, PAI students come from various regions in Indonesia and some are from overseas, Third, the curriculum applied based on Decree of the Ministry of National Education No. 045 / U / 2002 KIPT With the main competencies of insight, intellectual, social, appreciative, democratic, and active role in the society Fourth, the structure of PAI study program based on Permenag RI No. 8 of 2005 on Organizational Structure and Work Procedure of UIN and Fifth, alumni to various regions in Indonesia, was developed by Alumni Association of Alumni of Study Program which was chaired by Dr. H. Nashruddin, M Ag. Career distribution 86.5% become teachers, 3.8% entrepreneurs, 7.7% of employees, and 2.0% to housewives and fathers. Keywords: Role of alumni of Islamic State Islamic College, the society in accordance, with their profession.